Multiplikasi Anggrek Hitam ( Coelogyne pandurata Lindl ) Pada Media Murashige Skoog (Ms) Dengan Penambahan Ekstrak Pisang Ambon dan Benzyl Amino Purin (BAP) - Elvi Rusmiyanto P.W, Nurfadilah Mukarlina (Universitas Tanjungpura, 2018)
Black orchids (Coelogyne pandurata Lindl.) are epiphytic and endemic in Borneo. Habitat damage and over exploitation by the society can cause black orchids to be threatened with extinction. For this reason, alternative ways to increase black orchids are needed through tissue culture techniques with the addition of ambon banana extract and Benzyl Amino Purine BAP. The aim of this study was to determine the effect of ambon banana extract and BAP on the multiplication of black orchids. This research was conducted for 3 months from January to March 2018 at Pontianak Aloe Vera Center (AVC) Tissue Culture Laboratory. This study uses a Completely Randomized Design (CRD) with two factors. The first factor was ambon banana extract (0%; 2,5%; 5%; 7,5% and 10%) and the second factors BAP (0 M; 10-7M; 10-6M; 5x10-6M) with 3 replications, each of which obtained 60 trial unit. The results showed that the ambon banana extract had a significant effect on the time of budding, number of buds and number of leaves. The concentration of ambon banana extract 2,5% resulted in the fastest budding time appearing on the 11,33th day, the number of buds was 8,33 tillers, and the number of leaves was 17,67 strands.